Pelatihan Tekhnik Pengurangan Rasa Nyeri Persalinan Pada Ibu Hamil Dengan Metode Terapi Komplementer Di PMB Istri Yuliani Ngaglik Sleman D.I Yogyakarta - Rahayu, Puspito Panggih; Febriati, Listia Dwi (Universitas Respati Yogyakarta, 2020)
The paradigm of midwifery services has now shifted. Midwifery care is carried out in a combination of conventional and complementary midwifery services, and has become an important part of midwifery practice (Harding & Foureur, 2009). Childbirth in the First Stage caused pain experienced by maternity. One way to reduce pain in labor with complementary therapies include aromatherapy, relaxation therapy, music therapy and massage. The benefits of complementary therapy are that it helps increase relaxation while practicing breathing which is beneficial in labor and helps calm the mother, maintain the strength of the uterus during childbirth, help with breathing, and lower blood pressure. PMB Yuliani's wife is one of the Midwife's Independent Practices in the Sleman area that provides midwifery services and baby spa. Based on data obtained by Trimester III pregnant women still do not know the technique of pain reduction with complementary therapy methods. Objective: To provide training to pregnant women about pain reduction techniques with complementary therapy. Methods: conducted with counseling, lectures and frequently asked questions and practices (complementary therapy training). Community service activities carried out with counseling and training activities for Trimester III pregnant women for 3 days (20-22 August 2019). The activity was carried out for Pregnant Women at PMB Wife Yuliani Ngaglik Sleman D.I Yogyakarta. TheÂ participants seemed very relaxed and experienced the hypnobirthing process, because this was the experience of the participants for the first time getting this training. Participants suggest holding routine therapeutic training with this complementary method because it is felt to be very useful and participants feel much calmer, relaxed and comfortable after attending complementary method therapy training.Keywords: Complementary, Pregnant Women